Assessing Inclusion of Muslim Foreign Workers in Johor’s Zakat System: Legal and Maqasid Perspective Framework - Mohammad Hidir Baharudin; Rahmawati Mohd Yusoff; Ahmad Safwan Yunos (Perbanas Journal of Islamic Economics and Business, 2026)
This study critically examines the inclusion of Muslim foreign workers in Johor’s zakat system, focusing on their dual role as zakat payers (muzakki) and recipients (mustahiq), employing a mixed-methods approach that utilises legal analysis alongside social empirical research. The responsibilities and rights of Muslim foreign workers as muzakki and mustahiq are evaluated through the lens of Islamic law in Johor, with the legal analysis comprising statutory interpretation and a literature review. Surveys of 100 Muslim foreign workers in Johor were conducted to collect empirical data on practical barriers to access and participation. The research concludes, within the context of Maqasid al-Shariah, that Muslim foreign workers who qualify for nisab and haul hold a religious obligation to pay zakat. Concurrently, those who are experiencing poverty or those in debt are entitled to receive zakat, which aligns with the Shariah’s objectives of safeguarding life, property, and dignity. The legal analysis focuses on the Enactment of Islamic Religious Administration of Johor 1978, which permits Muslims in Johor to collect zakat, irrespective of their citizenship. Furthermore, empirical data indicate low awareness and limited access to zakat services, despite the population in Johor reaching 100,000. This is supported by a survey of 100 Muslim foreign workers in Johor, which adds to the existing empirical data. The barriers identified in the study encompass legal obstacles, a lack of bilingual support within institutions, and institutions' unwillingness to acknowledge other nationals as potential zakat beneficiaries.